Rethinking my poetry pedagogy: An Autoethnographic self-study - Campbell, B (South African Journal of Higher Education, 2016)
In the English discipline within the university where I am a teacher educator of English, it is standard practice for pre-service teachers to write an evaluation on completion of a series of lectures. This self-study examines a collaborative exercise in which the lecturer and students jointly analysed student reflections in order to establish the efficacy of a series of poetry lectures. To reflect on one’s classroom practice is important for growth and as a teacher educator one should not only practice reflection but also encourage students to engage in the same. In this study I used students’ pre-lecture reflections in order to get a sense of the students’ lived experiences so as to have an idea as to how to approach my lectures. The post-lecture reflections were used to discuss, in collaboration with the students, what makes for an effective poetry lecture. Pre-service teacher educators should model good teaching practices and I have always held the belief that my teaching methodology is constructivist and that in the process I am being reflexive and modeling good practice. However, the intended message is not always that which is received in the way anticipated by the lecturer. This self-study highlights the importance of firstly reflective practice and secondly, working in collaboration with students in order to improve practice. Keywords: reflective practice, collaborative data analysis, constructivism, pre-service teachers, English education